PENCEGAHAN DAN PENANGGULANGAN PERDAGANGAN PEREMPUAN YANG BERORIENTASI PERLINDUNGAN KORBAN - DTP Kusumawardhani (LIPI Press, 2010)
According to the ‘push and pull’ factors of human trafficking, traffickers and recruiters take advantage of the legal vacuum and of socio-economic problems present in local areas. Unemployment, poverty, lack of education, gender discrimination and family violence are conditions that turn recruitment into an easy task ― especially when future victims are often recruited under false pretences and with false promises. Once recruited, these human beings are most frequently turned into traffickers’ commodities and end up as victims of forced labour and sexual exploitation.This paper intends to show the importance of proper help and protection for women as trafficking victims. ‘Best practices’ such as psychological, social and economic assistance both before and after repatriation to the country of origin, may help to empower victims and to protect them to avoid them for being involved in human trafficking. Moreover, the promotion of victims’ needs is essential for the promotion of human security, which should also be a target of the countertrafficking law enforcement. Keywords: human trafficking, trafficking victim protection, law enforcement.